Effect of Carbon and Nitrogen Sources on the Production of Biosurfactant by Pseudomonas fluorescens isolated from Mangrove Ecosystem - Govindammal, M (International Journal of Pharmaceutical & Biological Archive, 2014)
Effect of Carbon and Nitrogen Sources on the Production of Biosurfactant by Pseudomonas fluorescens isolated from Mangrove Ecosystem